The Companion Status and Anxiety on Third Trimester Pregnancy Mother - Nita Ardiani Hasanah; Arum Meiranny; Atika Zahria Arisanti (JURNAL KEBIDANAN, 2020)
Anxiety in pregnant women can have an impact on low birth weight and smaller head circumference in babies born and can interfere with cognitive performance during infancy and decrease brain volume in areas associated with learning and memory in children aged 6-8 years. The purpose of this study was to determine the relationship between companion status during pregnancy and third trimester pregnant women anxiety. This research design method is quantitative analytic with cross sectional approach. research subjects for trimester III pregnant women numbering 40 respondents at the Bangetayu Health Center in Semarang City from July-August 2019. The sampling technique used was purposive sampling with research instruments in the form of a questionnaire with Kruskal wallis test. There is a relationship between the companion status during pregnancy to the anxiety of pregnant women third trimester.